CancerSupportSource®: validation of a revised multi-dimensional distress screening program for cancer patients and survivors. - Buzaglo, Joanne S.; Zaleta, Alexandra K.; McManus, Shauna; Golant, Mitch; Miller, Melissa F. (Supportive Care in Cancer, 2020)
Purpose: To facilitate access to and provision of psychosocial care to cancer patients in the community, the Cancer Support Community (CSC) developed CancerSupportSource® (CSS), an evidence-based psychosocial distress screening program. The current study examined the psychometric properties and multi-dimensionality of a revised 25-item version of CSS, and evaluated the scale's ability to identify individuals at risk for clinically significant levels of depression and anxiety.Methods: CSS development and validation were completed in multiple phases. Exploratory factor analysis was completed with 1436 individuals diagnosed with cancer to examine scale dimensionality, and nonparametric receiver operating characteristic (ROC) curve analyses were used to determine scoring thresholds for depression and anxiety risk scales. Internal consistency reliability and convergent and discriminant validity were also examined. Confirmatory factor analysis and intraclass correlation coefficients were subsequently calculated with a separate sample of 1167 individuals to verify the scale factor structure and examine test-retest reliability.Results: Five factors were identified and confirmed: (1) emotional well-being, (2) symptom burden and impact, (3) body image and healthy lifestyle, (4) health care team communication, and (5) relationships and intimacy. Psychometric evaluation of the total scale and factors revealed strong internal consistency reliability, test-retest reliability, and convergent and divergent validity. Sensitivity of CSS 2-item depression and 2-item anxiety risk scales were .91 and .92, respectively.Conclusions: Results indicate that CancerSupportSource is a reliable, valid, multi-dimensional distress screening program with the capacity to screen for those at risk for clinically significant levels of depression and anxiety.